Properties and Analysis of Transparency Conducting AZO Films by Using DC Power and RF Power Simultaneous Magnetron Sputtering - Neng-Fu Shih; Jin-Zhou Chen; Yeu-Long Jiang (Advances in Materials Science and Engineering)
DC power and RF power were introduced into the magnetic controlled sputtering system simultaneously to deposit AZO films in order to get an acceptable deposition rate with high quality transparency conducting thin film. The resistivity decreases with the RF power for the as-deposited samples. The resistivity of 6 × 10−4 Ω-cm and 3.5–4.5 × 10−4 Ω-cm is obtained for the as-deposited sample, and for all annealed samples, respectively. The transmittance of the AZO films with higher substrate temperature is generally above 80% for the incident light wavelength within 400–800 nm. The transmittance of the as-deposited samples reveals a clear blue shift phenomenon. The AZO films present (002) oriented preference as can be seen from the X-ray diffraction curves. All AZO films reveal compressive stress. The annealing process improves the electrical property of AZO films. A significant blue shift phenomenon has been found, which may have a great application for electrode in solar cell.